Quantitative Structure-Property Relationship Analysis for Optical Limiting of Organic Compounds Based on Genetic Algorithm Multivariate Linear Regression - Xu, Jie; Zhang, Hui; Wang, Luoxin; Xu, Weilin; Yi, Changhai; Liang, Hao; Li, Zengchang (Asian Journal of Chemistry, 2010)
The quantitative structure-property relationship (QSPR) treatment for optical limiting responses of organic compounds was performed by means of a genetic algorithm based multivariate linear regression (GA-MLR). A four-parameter model (R2 = 0.955 and s = 2.28) was established to predict the output energy (Iout). By this correlation, the optical limiting responses could be calculated with satisfactory accuracy. All descriptors involved in the model were derived directly from the molecular structures.